AB0831 COMPARISON OF DIFFERENT REMISSION INDICES IN PATIENTS WITH PSORIATIC ARTHRITIS: A POST HOC ANALYSIS OF DATA FROM PHASE 3 TOFACITINIB STUDIES. (2nd June 2020) - Schneeberger, E.; Citera, G.; Nash, P.; Smolen, J. S.; Mease, P. J.; Soriano, E.; Helling, C.; Szumski, A. E.; Mundayat, R.; Graham, D.; Ponce de Leon, D.
Abstract : Background: An international task force has agreed that remission and low disease activity (LDA) are treatment targets for patients (pts) with PsA, and recommends the Disease Activity Index in Psoriatic Arthritis (DAPSA) and minimal disease activity (MDA) to assess disease activity states. 1 Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. Objectives: In this post hoc analysis, we compared DAPSA LDA with MDA, and DAPSA remission with very low disease activity (VLDA) and DAS28-3(CRP) remission, in pts with PsA receiving tofacitinib. Methods: Data were pooled from 2 Phase 3 studies (OPAL Broaden [12 months; NCT01877668 ]; OPAL Beyond [6 months; NCT01882439 ]) for pts receiving tofacitinib 5 or 10 mg twice daily (BID) or placebo (PBO). DAPSA was determined by summing: swollen joint count (SJC66); tender/painful joint count (TJC68); Patient's Global Assessment of Arthritis (PtGA; visual analogue scale [VAS]); pain (VAS); and CRP. Pts were classified as achieving MDA or VLDA when meeting ≥5 (MDA) or 7 (VLDA) of the following criteria: TJC68 ≤1; SJC66 ≤1; Psoriasis Activity and Severity Index ≤1 or body surface area ≤3%; pain (VAS) ≤15; PtGA (VAS) ≤20; HAQ-DI ≤0.5; tender entheseal points (using Leeds Enthesitis Index [LEI]) ≤1. A logistic regression model was used to assess demographic and baseline characteristics as predictors of a trend in DAPSA scores at Month (M)3. DAPSA LDA (≤14), MDA, DAPSA remission (DAPSA ≤4), VLDA and DAS28-3(CRP) remission (DAS28-3[CRP]<2.6) rates were compared at M1, M3 and M6 for pts receiving tofacitinib 5 mg BID and at M6 for pts receiving tofacitinib 5 or 10 mg BID. Agreement between disease activity indices at M6 was evaluated using a kappa test. The percentage of tofacitinib-treated pts who achieved MDA, VLDA and non-response was reported at M6, stratified by achievement of DAPSA LDA, remission or non-response. Results: This analysis included 709 pts: tofacitinib 5 mg BID, n=237; tofacitinib 10 mg BID, n=236; PBO, n=236. At M3, older patients treated with tofacitinib, and tofacitinib- or PBO-treated pts with higher baseline SJC66, TJC68, PtGA VAS, HAQ-DI, LEI and Pain VAS, were significantly (p<0.05) more likely to have higher DAPSA. DAPSA LDA, MDA, remission (DAPSA and DAS28-3[CRP]) and VLDA rates generally increased from M1 to M6 for patients receiving tofacitinib 5 mg BID (Figure a). At M6, most tofacitinib-treated pts who achieved MDA, and all who achieved VLDA, were also in DAPSA remission or LDA (Figure b). At least moderate agreement (defined by kappa values 0.41–0.60) was observed between DAPSA LDA and MDA, and between DAPSA remission and VLDA, with both doses of tofacitinib at M6 (Figure c). Conclusion: Remission and LDA rates generally increased over time in pts with PsA receiving tofacitinib. DAPSA LDA showed moderate agreement with MDA, and DAPSA remission showed at least moderate agreement with VLDA, confirming that DAPSA and MDA are useful measurement tools to assess disease activity in pts with PsA treated with tofacitinib. References: [1]Smolen et al. Ann Rheum Dis 2018;77:3-17. Acknowledgments: Study sponsored by Pfizer Inc. Medical writing support was provided by Sarah Piggott of CMC Connect, McCann Health Medical Communications, and funded by Pfizer Inc. Disclosure of Interests: Emilce Schneeberger: None declared, Gustavo Citera Grant/research support from: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Consultant of: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Enrique Soriano Grant/research support from: AbbVie, Eli Lilly, GlaxoSmithKline, Novartis, Pfizer Inc, Sandoz, Consultant of: AbbVie, Eli Lilly, GlaxoSmithKline, Novartis, Pfizer Inc, Sandoz, Speakers bureau: AbbVie, Amber, Bristol-Myers Squibb, Eli Lilly, Novartis, Pfizer Inc, Roche, Claudia Helling Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Annette E Szumski Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Rajiv Mundayat Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Daniela Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Dario Ponce de Leon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc